Constraints from handedness on the evolution of brain lateralization - Martin, M; Jones, G (2005)
Can we understand brain lateralization in humans by analysis in terms of an evolutionarily stable strategy? The attempt to demonstrate a link between lateralization in humans and that in, for example, fish appears to hinge critically on whether the isomorphism is viewed as a matter of homology or homoplasy. Consideration of human handedness presents a number of challenges to the proposed framework.